Extraction of Oil from Azadirachta indica and Moringa stenopetala Seeds and Evaluation of its Physicochemical Properties - Degnechew Genene (MANAS: Journal of Engineering)
Azadirachta indica and Moringa stenopetala trees have been regarded as underutilized, tropical plants, fast-growing, drought-tolerant, robust, oleaginous, and evergreen perennial trees growing widely in various regions of Ethiopia. Almost every part of these plants (i.e., roots, stems, foliage, seeds, and barks) can be used as food additives and as raw materials for pharmaceuticals, cosmetics, soap, and biofuel processing industries. This study aimed at the extraction and characterization of oil from A. indica and M. stenopetala seeds using the solvent method. The Box-Behnken Design was employed in the experimental design and result analysis. The particle size (0.2, 0.5, 0.8 mm), solvent-to-solute ratio (3:1, 6:1, 9:1), and extraction time (2, 5, 8 hrs) were experimental variables with three levels of low, medium, and high, whereas, the extraction temperature was kept uniform. Seventeen experiments were conducted for each species thereby developing the quadratic models with a P-value < 0.0001(significant). The quality and adequacy of the models were evaluated by analysis of variance (ANOVA) at 5% least significant difference. Results of the physicochemical determination of oils were triplicated and obtained as mean ± standard deviation. The determined physicochemical properties of A. indica and M. stenopetala seed oils were kinematic viscosity, specific gravity, pH value, refractive index, acid value, free fatty acid, saponification value, iodine value, and peroxide value. The obtained experimental results showed that the extracted oils from A. indica and M. stenopetala seeds exhibit good oil quality, and hence, they can be employed for commercial and industrial purposes, and the generation of renewable energy (biofuel).